Grain gradient hard alloy holding-up hammer as well as preparation method and application thereof
By adopting a grain gradient structure cemented carbide top hammer, using the combination of matrix material and toughened matrix material, the problem of existing top hammers being prone to defects in the production process is solved, and the consumption of top hammers and the service life is achieved. Effect.
Patent Information
- Application Number
- CN202411611196.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-11
AI Technical Summary
The existing cemented carbide top hammers are prone to compression defects and sintering defects during the production process, resulting in short life and high consumption of top hammers, and abnormal hammer collapse and cracking hammers are prone to occur during diamond synthesis.
The grain gradient structure cemented carbide top hammer is used. Its material consists of matrix material and toughened matrix material. The matrix material forms the upper part of the top hammer and the toughened matrix material forms the lower part of the top hammer. It is prepared by layered powdering and molding and pressing. , grinding after sintering.
It reduces production difficulty and production costs, reduces the consumption of top hammers in diamond synthesis, reduces hammer consumption by 20%, and the average number of industrial diamond synthesis can reach more than 20,000 times, while avoiding the occurrence of pressing and sintering defects.
Smart Images

Figure CN119410994A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cemented carbide, and in particular relates to a cemented carbide top hammer with a grain gradient structure and a preparation method and application thereof. Background Art
[0002] At present, the large-scale industrial production of artificial diamond mainly adopts the high temperature and high pressure method (HPHT), and the synthesis of artificial diamond is usually carried out in a cubic high temperature and high pressure chamber surrounded by 6 top hammers. In the production cost of synthetic diamond by the high temperature and high pressure method: other auxiliary materials such as pyrophyllite, catalyst, plugs, etc. are determined by the number of blocks and basically cannot be changed; only the consumption of the top hammer is a major variable, and the consumption of the top hammer often accounts for the highest proportion of the total production cost, which directly affects the benefits of the enterprise. The gradient structure top hammer is considered to be an effective way to increase the life of the top hammer and reduce the consumption of the top hammer.
[0003] Chinese patent CN1154267A discloses a cemented carbide top hammer with an inner and outer and upper and lower cobalt gradient structure. The key preparation step is layered powder spreading. The structural feature is that the cobalt content in the height direction of the top hammer gradually increases from 5-7.5wt% at the top of the top hammer to 7-9wt% at the bottom, and the cobalt content along the radial direction of the cross section gradually increases from 5-7.5wt% in the center to 7-9wt% at the periphery.
[0004] US Patent No. 5780139A discloses a gradient structure cemented carbide top hammer, the preparation process of which is: placing cemented carbide mixtures of different particle sizes and cobalt contents in a mold by layered powder spreading, pressing and sintering, and combining cemented carbide layers with different properties. The characteristics of the gradient structure top hammer are: having multiple gradient transition layers, and the matrix on both sides of the gradient transition layer is discontinuous.
[0005] When conventional processes are used to produce cemented carbide top hammers, pressing defects are very likely to occur on the large and small bevel surfaces of the top hammer. The above two patents use a layered powdering method to press and sinter cemented carbide mixtures of different particle sizes and different cobalt contents, which will further increase the probability of pressed cracks on the large and small bevel surfaces. During the sintering process, cobalt aggregation and unstable bonding between tungsten carbides are also very likely to occur in the transition zone of different mixtures. In the process of synthesizing diamonds, the large and small bevel surfaces of the top hammer are high-risk points for failure of the top hammer, and the transition zone of the gradient structure of the top hammers of the above two patents has parts located on the large or small bevel surfaces, and industrialization faces huge challenges.
[0006] Chinese patent CN115845734A discloses a gradient structure cemented carbide top hammer containing tough particles. One of its characteristics is that the transition zone is located in the top hammer column part which is simple in shape and not prone to cracks. The second characteristic is that the matrix material on both sides of the transition zone accounts for a high proportion, and the matrix material is in a continuous state. Therefore, the top hammer of this patent is not prone to defects such as cracks and delamination during the pressing and sintering process, which is conducive to industrial implementation. However, it has the problems of more preparation steps and higher costs. It is necessary to prepare three kinds of mixtures: matrix mixture, tough particle mixture and matrix mixture containing tough particles, and then load, press, sinter and grind them in layers. Summary of the invention
[0007] Based on the above, the main purpose of the present invention is to provide a grain gradient cemented carbide top hammer and its preparation method and application.
[0008] To this end, in a first aspect, the present invention proposes a grain gradient cemented carbide top hammer, wherein the cemented carbide top hammer material includes a matrix material and a toughened matrix material, wherein the matrix material constitutes the upper part of the top hammer, and the toughened matrix material constitutes the lower part of the top hammer;
[0009] The tungsten carbide in the matrix material is first tungsten carbide, and the grain size of the first tungsten carbide is 0.8-1.2 μm; the tungsten carbide in the toughened matrix material is first tungsten carbide and second tungsten carbide, and the grain size of the second tungsten carbide is 2.0-3.2 μm.
[0010] In the present invention, the radial volume of the upper half of the top hammer and the small bevel, large bevel and upper half of the cylinder is formed by the matrix material, while the radial volume of the lower half of the top hammer and the lower half of the cylinder is formed by the toughened matrix material.
[0011] The toughened matrix material of the present invention adds a second tungsten carbide with a larger grain size into the matrix material, thereby increasing the toughness of the toughened matrix material.
[0012] In the present invention, the matrix material constitutes the upper part of the top hammer, and the toughened matrix material constitutes the lower part of the top hammer, so the grain gradient transition zone is also the tungsten carbide grain size change zone, and is also the transition zone between hardness and toughness; the grain gradient transition zone is located in the top hammer column body part, which is conducive to reducing production difficulty and production cost. The top hammer column body part has a simple shape, and it is not easy to produce pressing defects such as cracks and delamination during pressing. At the same time, since the WC grain size and cobalt content of the matrix on both sides of the transition zone are consistent, the continuous state of the matrix is not destroyed by the second tungsten carbide in the toughened matrix material at the bottom of the top hammer. Compared with the existing gradient cemented carbide top hammer, the gradient structure transition zone of the present invention is not easy to have pressing and sintering defects.
[0013] In the present invention, since the material of the lower part of the top hammer is a toughened matrix material with relatively high toughness, the toughness of the lower part of the top hammer can be increased, thereby avoiding the abnormal hammer collapse and hammer cracking phenomenon during the diamond synthesis and pressure boosting process, and can timely and effectively absorb part of the impact force of the top hammer when the top hammer cracks, effectively reducing the consumption of the top hammer during the diamond synthesis and pressure boosting process, the hammer consumption is reduced by 20%, and the average synthesis times of industrial diamonds can reach more than 20,000 times.
[0014] As a specific embodiment of the present invention, the cobalt content in the matrix material is 6-12wt%, the inhibitor content is 0.2-0.6wt%, and the balance is the first tungsten carbide; the cobalt content in the toughened matrix material is 6-12wt%, the inhibitor content is 0.2-0.6wt%, the second tungsten carbide is 5-30wt%, preferably 10-25wt%, and the balance is the first tungsten carbide. When the components in the matrix material and the toughened matrix material are within the above-mentioned proportion range, the toughness of the material at the bottom of the top hammer can be further improved, thereby better avoiding the abnormal collapse of the hammer and the cracking of the hammer during the diamond synthesis boosting process, and can timely and effectively absorb part of the impact force when the top hammer is cracked, effectively further reducing the consumption of the top hammer during the diamond synthesis boosting process.
[0015] As a specific embodiment of the present invention, the inhibitor includes Cr 3 C 2 and optional VC, and Cr 3 C 2 Content ≥ VC content.
[0016] As a specific implementation of the present invention, the hardness of the upper portion of the top hammer is 0.2 to 2.0 HRA higher than the hardness of the lower portion of the top hammer.
[0017] As a specific embodiment of the present invention, the fracture toughness of the lower part of the top hammer is 0.5 to 3.0 MPa*m1 / 2 higher than the fracture toughness of the upper part of the top hammer.
[0018] As a specific implementation of the present invention, the height of the lower portion of the top hammer is 1 to 30% of the total height of the top hammer, preferably 20 to 30%.
[0019] As a specific implementation of the present invention, the hardness of the top hammer is 90.0-93.0 HRA.
[0020] As a specific implementation of the present invention, the fracture toughness of the top hammer is 8 to 15 MPa*m1 / 2.
[0021] To this end, in a second aspect, the present invention provides a method for preparing a grain gradient cemented carbide top hammer, comprising the following steps:
[0022] S1: mixing a first tungsten carbide powder, a cobalt powder and an inhibitor powder to prepare a mixture A;
[0023] S2: preparing a mixture B by mixing the first tungsten carbide powder, the second tungsten carbide powder, the cobalt powder and the inhibitor powder;
[0024] S3: The mixed material A obtained in step S1 and the mixed material B obtained in step S2 are loaded in layers, and molded to obtain a gradient structure cemented carbide anvil blank;
[0025] S4: Sintering, rough grinding and fine grinding the gradient structure cemented carbide top hammer compact obtained in step S3 to obtain a gradient structure top hammer finished product.
[0026] The preparation method of the present invention has simple preparation procedures and low cost. It only needs to prepare two mixed materials first, and then load them in layers, press, sinter and grind them. In addition, the two mixed materials have similar compositions and are easy to prepare.
[0027] As a specific embodiment of the present invention, the preparation conditions of the mixture A and the mixture B are the same or different, and each independently includes: ball milling for 30 to 60 hours, filtering, and then spray drying, an atomization pressure of 1.0 to 1.2 MPa, and a spray tower outlet temperature of 95 to 100°C.
[0028] As a specific embodiment of the present invention, the mass ratio of tungsten carbide powder, cobalt powder and inhibitor powder in the mixtures A and B is 87.4-93.8:6-12:0.2-0.6.
[0029] As a specific embodiment of the present invention, the mass ratio of the first tungsten carbide powder to the second tungsten carbide powder in the mixture B is 70-95:5-30, preferably 75-90:10-25. The first tungsten carbide powder and the second tungsten carbide powder within the above ratio range can further improve the toughness of the material at the bottom of the top hammer, thereby better avoiding the abnormal collapse of the hammer and the cracking of the hammer during the diamond synthesis boosting process, and can timely and effectively absorb part of the impact force when the top hammer is cracked, effectively further reducing the consumption of the top hammer during the diamond synthesis boosting process.
[0030] As a specific embodiment of the present invention, in step S3, the pressing pressure is 100-200 MPa.
[0031] As a specific embodiment of the present invention, in step S4, the sintering conditions include: a sintering temperature of 1380-1480° C., a sintering pressure of 5-10 MPa, and a holding time of 0.5-3 h.
[0032] As a specific implementation of the present invention, in step S4, the rough grinding and fine grinding conditions include: firstly rough grinding with a grinding depth of 0.015 to 0.025 mm; and then fine grinding with a grinding depth of 0.005 to 0.015 mm.
[0033] To this end, in a third aspect, the present invention proposes an application of the above-mentioned grain gradient cemented carbide top hammer or the grain gradient cemented carbide top hammer prepared by the above-mentioned preparation method in the field of artificial diamond synthesis.
[0034] The final product shape and position tolerance, roughness, etc. of the grain gradient cemented carbide top hammer provided by the present invention meet the requirements of the national standard YS / T503-2020.
[0035] The beneficial effects of the present invention are:
[0036] 1. The gradient structure cemented carbide anvil of the present invention has a gradient structure transition zone located in the anvil column body, which is conducive to reducing production difficulty and production cost. The anvil column body has a simple shape, and is not prone to cracks, delamination and other pressing defects during pressing. At the same time, since the WC grain size and cobalt content of the matrix on both sides of the transition zone are consistent, the continuous state of the matrix is not destroyed by the toughened coarse-grained WC (i.e., the second tungsten carbide) in the lower part of the anvil. Compared with the existing gradient cemented carbide anvil, the gradient structure transition zone of the present invention is not prone to pressing and sintering defects.
[0037] 2. The lower part of the gradient structure cemented carbide top hammer of the present invention is added with tough coarse WC. During the diamond synthesis and pressure boosting process, abnormal hammer collapse and hammer cracking phenomena occur. Due to the high toughness of the lower part of the top hammer, part of the impact force of the top hammer cracking can be timely and effectively absorbed, thereby effectively reducing the consumption of the top hammer during the diamond synthesis and pressure boosting process. The hammer consumption is reduced by 20%, and the average synthesis times of industrial diamonds can reach more than 20,000 times.
[0038] 3. Compared with the existing gradient top hammer technology, the present invention is less likely to have cracks, delamination waste and organizational structure defects during the pressing and sintering process, has small quality fluctuations, is easy to control, and is conducive to industrial implementation. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1a This is a schematic cross-sectional view of the grain gradient cemented carbide top hammer obtained in Example 1 of the present invention.
[0040] Figure 1b This is a metallographic diagram of the upper material of the grain gradient cemented carbide top hammer obtained in Example 1 of the present invention.
[0041] Figure 1c This is a metallographic diagram of the lower material of the grain gradient cemented carbide top hammer obtained in Example 1 of the present invention.
[0042] Figure 2 It is a Rockwell hardness distribution diagram based on the cross section along line AA in Figure 1.
[0043] Figure 3 It is the fracture toughness distribution diagram based on the section along line AA in Figure 1. DETAILED DESCRIPTION
[0044] The technical scheme of the present invention is further described below by specific embodiments. Those skilled in the art should understand that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.
[0045] In each embodiment of the present invention, the hardness is obtained by using the HRA Rockwell hardness test method, and the test standard is ISO 3738; the fracture toughness is obtained by using the Barcol indentation method, and the test standard is ISO 28079-2009.
[0046] Example 1
[0047] This embodiment provides a gradient structure cemented carbide anvil and a preparation method thereof, and the specific steps are as follows:
[0048] S1: The upper part of the top hammer is made of a matrix material, which is composed of 91.5wt% WC (grain size 1.2μm, matrix WC is also called first WC) and 0.5wt% Cr 3 C 2 , 8wt% Co were weighed and wet-milled in a ball mill with a ball-to-material mass ratio of 4:1. Alcohol was selected as the ball-milling medium, and 360ml of alcohol was added per kilogram of raw material. Paraffin was selected as the molding agent, and 20g of paraffin was added per kilogram of raw material. After ball milling for 43h, it was filtered and spray-dried to obtain a matrix mixture A.
[0049] S2: The lower part of the top hammer is made of a toughened matrix material, which is composed of 73.2wt% WC (grain size 1.2μm, matrix WC is also called the first WC), 18.3wt% WC (grain size 2.4μm, toughened WC is also called the second WC), and 0.5wt% Cr 3 C 2 , 8wt% Co were weighed and wet-milled in a ball mill with a ball-to-material mass ratio of 4:1. Alcohol was selected as the ball-milling medium, 360ml of alcohol was added per kilogram of raw material. Paraffin was selected as the molding agent, 20g of paraffin was added per kilogram of raw material. After ball milling for 43h, it was filtered and spray-dried to obtain a matrix mixture B.
[0050] S3: Load the matrix mixture A and the matrix mixture B in layers, with the loading height of the matrix mixture B being 30% of the total loading height, and press molding at a pressing pressure of 150 MPa.
[0051] S4: Finally, the conventional top hammer production process is followed to perform sintering, rough grinding, and fine grinding to obtain a gradient structure top hammer. The sintering temperature is 1450°C, the sintering pressure is 8MPa, and the holding time is 2h; the 80# grinding wheel is used for rough grinding, and the grinding depth is 0.02mm; the 240# grinding wheel is used for fine grinding, and the grinding depth is 0.01mm.
[0052] The shape and position tolerance and roughness of the gradient structure cemented carbide top hammer obtained in Example 1 meet the requirements of the national standard YS / T 503-2020. Figure 1(b) is a metallographic image of the upper material of the top hammer; Figure 1(c) shows a metallographic image of the lower material of the top hammer, which contains some medium-coarse WC grains, and the maximum size of the medium-coarse WC grains is less than 10μm; the performance test shows that the hardness of the top hammer is 91.2 at the upper part and 91.0 at the lower part. Figure 2 As shown in the figure, the fracture toughness of the upper part of the top hammer is 11.5, and that of the lower part is 12.6. Figure 3 The test results are shown in Table 1.
[0053] Example 2
[0054] This embodiment provides a gradient structure cemented carbide anvil and a preparation method thereof, and the specific steps are as follows:
[0055] S1: The upper material is 91.6wt% WC (grain size 1.2μm, matrix WC), 0.2wt% Cr 3 C 2 , 0.2wt% VC, and 8wt% Co were weighed and wet-milled in a ball mill with a ball-to-material mass ratio of 4:1. Alcohol was selected as the ball-milling medium, and 360ml of alcohol was added per kilogram of raw material. Paraffin was selected as the molding agent, and 20g of paraffin was added per kilogram of raw material. After ball-milling for 50 hours, it was filtered and spray-dried to obtain a matrix mixture A.
[0056] S2: The lower material is 77.9wt% WC (grain size 1.2μm, matrix WC), 13.7wt% WC (grain size 3.2μm, toughening WC), 0.2wt% Cr 3 C 2 , 0.2wt% VC, and 8wt% Co were weighed and wet-milled in a ball mill with a ball-to-material mass ratio of 4:1. Alcohol was selected as the ball-milling medium, and 360ml of alcohol was added per kilogram of raw material. Paraffin was selected as the molding agent, and 20g of paraffin was added per kilogram of raw material. After ball-milling for 50 hours, it was filtered and spray-dried to obtain a matrix mixture B.
[0057] S3: Load the matrix mixture A and the matrix mixture B in layers, with the loading height of the mixture B being 20% of the total loading height, and the pressing pressure being 165 MPa for compression molding.
[0058] S4: Finally, the gradient structure top hammer is prepared by sintering, rough grinding and fine grinding according to the conventional top hammer production process. The sintering temperature is 1450℃, the sintering pressure is 8.5MPa, and the holding time is 2h; the rough grinding is performed with an 80# grinding wheel, and the grinding depth is 0.02mm; the fine grinding is performed with a 240# grinding wheel, and the grinding depth is 0.01mm.
[0059] Example 3
[0060] This embodiment provides a gradient structure cemented carbide anvil and a preparation method thereof, and the specific steps are as follows:
[0061] S1: The upper material is 89.5wt% WC (grain size 0.8μm, matrix WC), 0.5wt% Cr 3 C 2 , 10wt% Co material was weighed and wet-ground in a ball mill with a ball-to-material mass ratio of 5.5:1. Alcohol was selected as the ball-milling medium, and 380ml of alcohol was added per kilogram of raw material. Paraffin was selected as the molding agent, and 21g of paraffin was added per kilogram of raw material. After ball-milling for 50h, it was filtered and spray-dried to obtain a matrix mixture A.
[0062] S2: The lower material is 71.6wt% WC (grain size 0.8μm, matrix WC), 17.9wt% WC (grain size 2.0μm, toughening WC), 0.5wt% Cr 3 C 2 , 10wt% Co material was weighed and wet-milled in a ball mill with a ball-to-material mass ratio of 5.5:1. Alcohol was selected as the ball milling medium, and 380ml of alcohol was added per kilogram of raw material. Paraffin was selected as the molding agent, and 21g of paraffin was added per kilogram of raw material. After ball milling for 50h, it was filtered and spray-dried to obtain a matrix mixture B.
[0063] S3: Load the matrix mixture A and the matrix mixture B in layers, with the loading height of the matrix mixture B being 20% of the total loading height, and performing compression molding at a pressing pressure of 170 MPa.
[0064] S4: Finally, the gradient structure top hammer is prepared by sintering, rough grinding and fine grinding according to the conventional top hammer production process. The sintering temperature is 1400℃, the sintering pressure is 6MPa, and the holding time is 1.5h; the rough grinding is performed with an 80# grinding wheel, and the grinding depth is 0.02mm; the fine grinding is performed with a 240# grinding wheel, and the grinding depth is 0.01mm.
[0065] The shape and position tolerance and roughness of the gradient structure cemented carbide top hammer obtained in Example 3 meet the requirements of the national standard YS / T 503-2020. The performance test was carried out and the test results are shown in Table 1.
[0066] Example 4
[0067] This embodiment provides a gradient structure cemented carbide anvil and a preparation method thereof, and the specific steps are as follows:
[0068] S1: The upper material is 89.5wt% WC (grain size 0.8μm, matrix WC), 0.3wt% Cr 3 C 2 , 0.2wt% VC, and 10wt% Co were weighed and wet-milled in a ball mill with a ball-to-material mass ratio of 6:1. Alcohol was selected as the ball-milling medium, and 380ml of alcohol was added per kilogram of raw material. Paraffin was selected as the molding agent, and 21g of paraffin was added per kilogram of raw material. After ball-milling for 55h, it was filtered and spray-dried to obtain a matrix mixture A.
[0069] S2: The lower material is 76.1wt% WC (grain size 0.8μm, matrix WC), 13.4wt% WC (grain size 2.4μm, toughening WC), 0.3wt% Cr 3 C 2 , 0.2wt% VC, and 10wt% Co were weighed and wet-milled in a ball mill with a ball-to-material mass ratio of 6:1. Alcohol was selected as the ball-milling medium, and 380ml of alcohol was added per kilogram of raw material. Paraffin was selected as the molding agent, and 21g of paraffin was added per kilogram of raw material. After ball-milling for 55h, it was filtered and spray-dried to obtain a matrix mixture B.
[0070] S3: Load the matrix mixture A and the matrix mixture B in layers, with the loading height of the matrix mixture B being 20% of the total loading height, and performing compression molding at a pressing pressure of 180 MPa.
[0071] S4: Finally, the gradient structure top hammer is prepared by sintering, rough grinding and fine grinding according to the conventional top hammer production process. The sintering temperature is 1410℃, the sintering pressure is 7MPa, and the holding time is 1.8h; the rough grinding is performed with 80# grinding wheel, and the grinding depth is 0.02mm; the fine grinding is performed with 240# grinding wheel, and the grinding depth is 0.01mm.
[0072] The shape and position tolerance and roughness of the gradient structure cemented carbide top hammer obtained in Example 4 meet the requirements of the national standard YS / T 503-2020. The performance test was carried out and the test results are shown in Table 1.
[0073] Example 5
[0074] This embodiment provides a gradient structure cemented carbide anvil and a preparation method thereof, and the specific steps are as follows:
[0075] S1: The upper material is 93.8wt% WC (grain size 1.2μm, matrix WC), 0.2wt% Cr 3 C 2, 6wt% Co were weighed and wet-milled in a ball mill with a ball-to-material mass ratio of 4:1. Alcohol was selected as the ball-milling medium, and 350ml of alcohol was added per kilogram of raw material. Paraffin was selected as the molding agent, and 20g of paraffin was added per kilogram of raw material. After ball milling for 37h, it was filtered and spray-dried to obtain a matrix mixture A.
[0076] S2: The lower material is 70.3wt% WC (grain size 1.2μm, matrix WC), 23.5wt% WC (grain size 3.2μm, toughening WC), 0.2wt% Cr 3 C 2 , 6wt% Co was weighed and wet-milled in a ball mill with a ball-to-material mass ratio of 4:1. Alcohol was selected as the ball-milling medium, 350ml of alcohol was added per kilogram of raw material. Paraffin was selected as the molding agent, 20g of paraffin was added per kilogram of raw material. After ball-milling for 37h, it was filtered and spray-dried to obtain a matrix mixture B.
[0077] S3: Load the matrix mixture A and the matrix mixture B in layers, with the loading height of the mixture B# being 25% of the total loading height, and the pressing pressure being 150 MPa, and molding by molding.
[0078] S4: Finally, the gradient structure top hammer is prepared by sintering, rough grinding and fine grinding according to the conventional top hammer production process. The sintering temperature is 1450℃, the sintering pressure is 8MPa, and the holding time is 2.0h; the rough grinding is performed with 80# grinding wheel, and the grinding depth is 0.02mm; the fine grinding is performed with 240# grinding wheel, and the grinding depth is 0.01mm.
[0079] The shape and position tolerance and roughness of the gradient structure cemented carbide anvil obtained in Examples 1-5 all meet the requirements of the national standard YS / T 503-2020. The performance tests were carried out respectively, and the test results are shown in Table 1.
[0080] Table 1
[0081]
[0082] Test Example 1
[0083] Conventional top hammer: The whole hammer adopts the material of the top hammer in Example 1: 91.5wt% WC-0.5wt% Cr 3 C 2 -8wt% Co, WC grain size 1.2μm. During the diamond synthesis boosting process, abnormal hammer phenomenon occurs, and the hammer sometimes cracks other top hammers that form the synthesis cavity with it, usually 1 with 0 to 1 with 3.
[0084] The top hammer of the present invention: using the grain gradient cemented carbide top hammer of Example 1, during the diamond synthesis and pressurization process, abnormal hammer collapse and hammer cracking phenomena occur. Since the lower part of the top hammer has higher toughness, it can timely and effectively absorb part of the impact force of the top hammer during the hammer cracking. The consumption of the top hammer during the hammer collapse and hammer cracking usually becomes 1 with 0 to 1 with 2, which can effectively reduce the consumption of the top hammer during the diamond synthesis and pressurization process.
[0085] In summary, the grain gradient cemented carbide anvil of the present invention has a gradient structure transition zone located in the anvil column body, which is conducive to reducing production difficulty and production cost. The anvil column body has a simple shape, and is not prone to cracks, delamination and other pressing defects during pressing. At the same time, since the WC grain size and cobalt content of the matrix material on both sides of the transition zone are consistent, the continuous state of the matrix is not destroyed by the toughened coarse-grained WC in the lower part of the anvil, so the generation of pressing defects in the gradient structure transition zone can be greatly reduced.
[0086] Any numerical value mentioned in the present invention includes all values that increase by one unit each time from the lowest value to the highest value if there is only an interval of two units between any minimum value and any maximum value. For example, if the amount of a component, or the value of a process variable such as temperature, pressure, time, etc. is declared to be 50-90, in this specification it means that 51-89, 52-88... and 69-71 and 70-71 are specifically listed. For non-integer values, 0.1, 0.01, 0.001 or 0.0001 can be appropriately considered as a unit. These are just some specially specified examples. In this application, in a similar manner, all possible combinations of numerical values between the listed lowest and highest values are considered to have been disclosed.
[0087] The above description of the embodiments is to facilitate the understanding and application of the present invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the embodiments herein, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.
Claims
1. A grain gradient cemented carbide top hammer, characterized in that: The material of the cemented carbide top hammer includes a base material and a toughened base material, wherein the base material constitutes the upper part of the top hammer, and the toughened base material constitutes the lower part of the top hammer; The tungsten carbide in the matrix material is first tungsten carbide, and the grain size of the first tungsten carbide is 0.8-1.2 μm; the tungsten carbide in the toughened matrix material is first tungsten carbide and second tungsten carbide, and the grain size of the second tungsten carbide is 2.0-3.2 μm.
2. The cemented carbide top hammer according to claim 1, characterized in that: The cobalt content in the matrix material is 6-12wt%, the inhibitor content is 0.2-0.6wt%, and the balance is the first tungsten carbide; the cobalt content in the toughened matrix material is 6-12wt%, the inhibitor content is 0.2-0.6wt%, the second tungsten carbide is 5-30wt%, preferably 10-25wt%, and the balance is the first tungsten carbide.
3. The cemented carbide top hammer according to claim 2, characterized in that: The inhibitor includes Cr3C2 and optionally VC, and the content of Cr3C2 is ≥ the content of VC.
4. The cemented carbide top hammer according to any one of claims 1 to 3, characterized in that: The hardness of the upper part of the top hammer is 0.2-2.0 HRA higher than the hardness of the lower part of the top hammer; and / or The fracture toughness of the lower part of the top hammer is 0.5 to 3.0 MPa*m1 / 2 higher than the fracture toughness of the upper part of the top hammer.
5. The cemented carbide top hammer according to any one of claims 1 to 4, characterized in that: The height of the lower part of the top hammer is 1 to 30% of the total height of the top hammer, preferably 20 to 30%.
6. The cemented carbide top hammer according to any one of claims 1 to 5, characterized in that: The hardness of the top hammer is 90.0-93.0 HRA, and / or the fracture toughness is 8-15 MPa*m1 / 2.
7. A method for preparing a gradient structure cemented carbide top hammer according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: mixing a first tungsten carbide powder, a cobalt powder and an inhibitor powder to prepare a mixture A; S2: preparing a mixture B by mixing the first tungsten carbide powder, the second tungsten carbide powder, the cobalt powder and the inhibitor powder; S3: The mixed material A obtained in step S1 and the mixed material B obtained in step S2 are loaded in layers, and molded to obtain a gradient structure cemented carbide anvil blank; S4: Sintering, rough grinding and fine grinding the gradient structure cemented carbide top hammer compact obtained in step S3 to obtain a gradient structure top hammer finished product.
8. The preparation method according to claim 7, characterized in that: The preparation conditions of the mixture A and the mixture B are the same or different, and each independently includes: Ball milling for 30 to 60 hours, followed by filtering and spray drying, with an atomization pressure of 1.0 to 1.2 MPa and a spray tower outlet temperature of 95 to 100°C; and / or The mass ratio of tungsten carbide powder, cobalt powder and inhibitor powder in the mixture A and B is 87.4-93.8:6-12:0.2-0.6; and / or The mass ratio of the first tungsten carbide powder to the second tungsten carbide powder in the mixture B is 70-95:5-30, preferably 75-90:10-25.
9. The preparation method according to claim 7 or 8, characterized in that: In step S3, the pressing pressure is 100-200 MPa; and / or In step S4, the sintering conditions include: sintering temperature of 1380-1480°C, sintering pressure of 5-10 MPa, and holding time of 0.5-3 h; and / or In step S4, the rough grinding and fine grinding conditions include: firstly performing rough grinding with a grinding depth of 0.015 to 0.025 mm; and then performing fine grinding with a grinding depth of 0.005 to 0.015 mm.
10. Use of the grain gradient cemented carbide top hammer according to any one of claims 1 to 6 or the grain gradient cemented carbide top hammer prepared by the preparation method according to any one of claims 7 to 9 in the field of synthetic diamond synthesis.
Citation Information
Patent Citations
Hard alloy top hammer for high pressure synthesizing diamond
CN1154267A
Impact-resistant hard alloy cubic anvil as well as preparation method and application thereof
CN115845734A
Multi-layer anvil for ultra high pressure presses
US5780139A